The Ideology Of Text “I Pucung”: Sytemic Functional Linguistics Perspective - Semadi, Yoga Putra; Suardana, I Ketut (International Journal of Linguistics and Discourse Analytics, 2024)
Balinese ancestors cared very much to the generation to achieve harmony in social communities so the Balinese ancestors always embedded moral value through many kinds og genre. One of Balinese genres that is used to embed moral values is Balinese Narrative text entitled “I Pucung”. The text contains semiotic so this research would like to explore the ideology of text “I Pucung”. This is qualitative research, phenomenology. The data were taken from clauses of the text “I Pucung” from Satua-Satua Bali. The Theory used for this research is Systemic Functional Linguistics. The technique used in this research is comprehending the text carefully based on social context which is held by Balinese communities. The result of this research shows the text is associated with Sad Ripu ‘six bad traits owned by human’, namely; greedy, overbearing, confused, jealous, lust, and angry. Those traits make human life destroyed. This text teaches us how to avoid behaving Sad Ripu in communities. In contrast, performing good traits in communities leads us to get harmony. This research brings positive impacts for semiotics, discourse analysis, teaching. This research is expected to be able to stimulate other linguistic researchers to explore ideology for other Balinese text